Impact of Endogenous Risk Factors on Risk Cost in PPP Projects in Saudi Arabia - Alfraidi, Y.; Alzahrani, S. M.; Abdelhafez, M. H. H.; Boussabaine, H. (Engineering, Technology & Applied Science Research, 2020)
The formation of the Public-Private Partnership (PPP) contracts is based on the grounds that the construction, progress, operation, and investment of a project must be allocated to a private organization under a contract. The risks associated with PPP projects are usually associated with resource improvement and development as well as the long-term operation of the project. It is known that cost and time overruns are among the obvious risks faced by a project during the development phase. Cost and time overruns are major sources of monetary risk. The risk and its impact may vary at different phases during the life cycle of a PPP project. In traditional procurement, all of the monetary risks are covered by the public sector. Most of the projects delivered under traditional procurement involve a price confirmation to indicate standard cost risks. This paper aims to investigate the impact of endogenous factors on budget overrun in PPP projects in Saudi Arabia. The paper briefly illustrates the content regarding the PPP risk evaluating systems and explains the association between risk occurrences and cost overrun in the Kingdom of Saudi Arabia (KSA). The paper concludes with recommendations for future research.